Performans rasta i hranjentna povećava od growernih svinja na kiši (Albizia saman) pods kao zamena za kukuruz: Response of growing pigs to dietary Albizia saman pods - Irekhore, Oluwakemi; Akinsoyinu, Akintunde; Bello, Kazeem (Journal of Agricultural Sciences (Belgrade), 2022)
Growth performance and nutrient digestibility of pigs fed diets containing raintree pods (RP) was evaluated using 20 growing pigs. Five diets were formulated with RP replacing maize in the control diet at 10, 20, 30 and 40% on weight for weight basis. The pigs were randomly allotted to the 5 dietary treatments, with 4 replicates of one (1) pig per replicate, and fed ad libitum for eight weeks. Data were collected on initial weight, final weight (FW), daily feed intake (DFI), daily weight gain (DWG), feed conversion ratio (FCR), cost per kilogramme feed (CKF) and feed cost per kilogramme weight gain. At week eight, the pigs were moved into individual metabolic crates for digestibility trial. Raintree pods, feed and faecal samples were analysed for proximate composition and metabolizable energy was calculated following standard procedures. Apparent digestibility of dry matter, crude protein, ether extract, ash, and nitrogen free extract were calculated. Data generated were analysed using one-way analysis of variance. Growth performance of pigs fed 10% RP diet was similar to those fed control diet. As dietary inclusion of RP increased, the DFI, DWG and FW of the pigs decreased (p